Pembentukan dan Peningkatan Kapasitas Kelompok Perukti Jenazah Perempuan - Siti Bahiroh; Talqis Nurdianto; Warih Andan Puspitosari (Universitas Muhammadiyah Yogyakarta, 2021)
Islam teaches that every human being will experience death. The obligation of a Muslim to a Muslim who dies is fard kifayah, meaning that if some Muslims have carried it out, then the obligations have finished. These obligations are bathing, shrouding, praying and burying the dead. Women’s bodies must be treated specifically by the female coroner’s team. Hamlet Kembaran already has several ladies who are active in the care of corpses, despite the limited number. Accordingly, it affects the treatment of female corpses, where they are often assisted and guided by male coroners. Thus, more female mortuary teams are necessary with the knowledge, skills and independence in caring for women’s corpses and psychological assistance for bereaved families through the formation of a women’s mortuary team in the Kembaran hamlet. The program aimed to increase the knowledge and skills of the women’s congregation in the care (rukti) of women’s bodies through tutorials and practices. The implementation of the methods was carried out online using video tutorials and practices. The participants were 30 women, members of the Babul Jannah recitation, who were willing to take part in the training. The training was carried out for one month by a service team with religious and psychological expertise. Also, the videos and modules were created by the team. The training was carried out online through the Whatsapp group by providing material in the form of modules, presentation slides and videos of corpse care practices. The results of this community service program indicated that the knowledge, skills and behavior of the women’s congregation improved significantly, and they are ready to practice the care (rukti) of women’s bodies independently.